Analisis penerapan manajemen risiko dalam meningkatkan kinerja keuangan pada perbankan syariah - syahlatunnisa, syifa (Maliki Interdisciplinary Journal, 2026)
This study aims to analyze the implementation of risk management in improving the financial performance of Islamic banking. Islamic banking, as a financial intermediary institution, plays an important role in the economy; however, it also faces various risks such as financing risk, operational risk, liquidity risk, and market risk. Therefore, the implementation of risk management becomes an essential aspect in maintaining the stability and sustainability of banking operations. The research method used in this study is a literature review by examining various relevant journals and previous studies. The results indicate that the implementation of risk management has a positive effect on the financial performance of Islamic banks, which is measured through profitability indicators such as Return on Assets (ROA). However, not all risk components have the same impact. Operational efficiency, proxied by BOPO, has been proven to have a significant effect on financial performance, while CAR and NPL do not always show significant effects. In addition, risk management also plays a role in improving organizational performance directly without necessarily being mediated by financial performance. Therefore, risk management can be considered a strategic factor in enhancing both financial and organizational performance in Islamic banking. The effective implementation of risk management must be carried out comprehensively through improving operational efficiency, strengthening governance, and developing human resources.